Nickel-mediated N–N bond formation and N2O liberation via nitrogen oxyanion reduction. Issue 31 (16th July 2021) - Beagan, Daniel M.; Cabelof, Alyssa C.; Pink, Maren; Carta, Veronica; Gao, Xinfeng; Caulton, Kenneth G.
Abstract : Deoxygenation of nitrogen oxyanions coordinated to nickel using reduced borylated heterocycles leads to N–N bond formation and N2 O liberation. The nickel dimer product facilitates NO disproportionation, leading to a synthetic cycle. Abstract : The syntheses of (DIM)Ni(NO3 )2 and (DIM)Ni(NO2 )2, where DIM is a 1, 4-diazadiene bidentate donor, are reported to enable testing of bis boryl reduced N-heterocycles for their ability to carry out stepwise deoxygenation of coordinated nitrate and nitrite, forming O(Bpin)2 . Single deoxygenation of (DIM)Ni(NO2 )2 yields the tetrahedral complex (DIM)Ni(NO)(ONO), with a linear nitrosyl and κ 1 -ONO. Further deoxygenation of (DIM)Ni(NO)(ONO) results in the formation of dimeric [(DIM)Ni(NO)]2, where the dimer is linked through a Ni–Ni bond. The lost reduced nitrogen byproduct is shown to be N2 O, indicating N–N bond formation in the course of the reaction. Isotopic labelling studies establish that the N–N bond of N2 O is formed in a bimetallic Ni2 intermediate and that the two nitrogen atoms of (DIM)Ni(NO)(ONO) become symmetry equivalent prior to N–N bond formation. The [(DIM)Ni(NO)]2 dimer is susceptible to oxidation by AgX (X = NO3 −, NO2 −, and OTf − ) as well as nitric oxide, the latter of which undergoes nitric oxide disproportionation to yield N2 O and (DIM)Ni(NO)(ONO). We show that the first step in the deoxygenation of (DIM)Ni(NO)(ONO) to liberate N2 O is outer sphere electron transfer, providing insight into the organic reductants employed for deoxygenation. Lastly, we show that at elevated temperatures, deoxygenation is accompanied by loss of DIM to form either pyrazine or bipyridine bridged polymers, with retention of a BpinO − bridging ligand.